Ink melanin from Sepiapharaonis ameliorates colitis in mice via reducing oxidative stress, andprotecting the intestinal mucosal barrier. (January 2022) - Xie, Jingwen; Liu, Lin; Li, Hongyan; Che, Hongxia; Xie, Wancui
Graphical abstract: Highlights: The effect of melanin from Sepiaesculenta in colitis was studied firstly. Melanin exhibited superior activity against inflammation and oxidation. Melanin significantly regulated the intestinal barrier and apoptosis. Melanin balanced the intestinal flora and metabolism affected by inflammation. Abstract: Melanin is the major component from Sepiapharaonis ink (MSI), and its anti-inflammatory and antioxidant activities indicate the potential for improvement of inflammatory bowel diseases. The study aimed to investigate how orally-administered MSI on alleviating the dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) and the potential mechanisms. We found that MSI significantly improved DSS-induced weight loss, colon shortening, hematochezia, DAI score, histopathology, and antioxidant indices (SOD and MDA). Further analysis demonstrated that MSI could significantly down-regulate the expression of pro-inflammatory cytokines (TNF-α, IL-1β and IFN-γ) and up-regulate the concentration of anti-inflammatory cytokine IL-10 by regulating TLR4/NF-κB and NLRP3/ASC/Caspase-1 signal pathway. Moreover, tight junction proteins in melanin groups were also maintained by ZO-1 and occludin expressions. In addition, MSI also regulated cellular apoptosis by reducing the expression of pro-apoptosis protein Caspase-3. Interestingly, MSI treatments increased the proportion of dominant bacteria (such as Bacteroidetes and Clostridium ) and the abundance of community (alpha diversity, β-diversity, etc.), which significantly balanced microbiota in a dose-dependent manner. In conclusion, oral administration of MSI alleviated DSS-induced colitis by modulating inflammatory cytokines and oxidation stress, maintaining the mucosal barrier, and reverting microbiota changes.